2019
DOI: 10.1101/623223
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spliced peptides and cytokine driven changes in the immunopeptidome of melanoma

Abstract: SummaryAntigen-recognition by CD8+ T cells is governed by the pool of peptide antigens presented on the cell surface in the context of HLA class I complexes. Recent studies have shown not only a high degree of plasticity in the immunopeptidome, but also that a considerable fraction of all presented peptides is generated through proteasome-mediated splicing of non-contiguous regions of proteins to form novel peptide antigens. Here we used high-resolution mass-spectrometry combined with new bioinformatic approac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 61 publications
1
32
0
Order By: Relevance
“…We believe that spliced peptides exist at a high prevalence, and we have recently shown their role in tumor antigen recognition (10).…”
mentioning
confidence: 99%
“…We believe that spliced peptides exist at a high prevalence, and we have recently shown their role in tumor antigen recognition (10).…”
mentioning
confidence: 99%
“…Dalet et al [28] and Paes et al [24] showed that with increasing the size of the intervening sequence, the probability of both forward and reverse cis-splicing decreases, although without being wholly abolished. However, this trend was not observed in data-orientated approaches [12,13,23]. Two proposed mechanisms for peptide splicing are (i) direct transpeptidation [3,6] and (ii) carboxylic acid and amine condensation [6].…”
Section: Spliced Peptide Generation -Mechanisms and Featuresmentioning
confidence: 94%
“…It has been suggested that peptide splicing is a stochastic process in the cell. However, we have recently found the repeated presentation of the same spliced peptides between biological replicates and even the same spliced peptides being presented by shared HLA alleles from different individuals [23]. It has also been shown in several in-vitro and in-cellulo experiments that both constitutive (standard) and immunoproteasomes can generate spliced peptides, with only slight differences in cleavage-site preferences [5,6,23].…”
Section: Spliced Peptide Generation -Mechanisms and Featuresmentioning
confidence: 99%
See 2 more Smart Citations